Wireless Indoor Positioning: Effective Deployment of Cells and Auto‐Calibration. (28th August 2013) - Barba, Félix Barba; Martin, Aaron Garrido; Fernández‐Durán, Alfonso; Urie, Alistair; Valenzuela, Reinaldo
Abstract Establishing a precise location for wireless users while they are indoors is currently an important challenge. The triangulation techniques used for external locations are useless due to adverse effects like the lack of line‐of‐sight or to multipath propagation. Fingerprinting methods, which are based on the comparison of received signal strength (RSS) values measured by the mobile phone with a radiomap of RSS values recorded during the calibration phase, currently offer the best methods for indoor scenarios. However, they are also affected by problems like channel variability. In this paper, we propose two ways to improve the systems based on fingerprinting methods. The first method minimizes negative effects resulting from inadequate deployment of the radio frequency emitters and describes a method to determine the minimum number and the best way to locate them from initial layout and accuracy requirements. The second method increases accuracy thanks to an automatic radiomap recalibration technique that leverages the measurements reported by a small number of static reference points, strategically deployed in an indoors environment. © 2013 Alcatel‐Lucent.